Implementation of Problem-Based Learning to Improve Cognitive Understanding and Quality of Learning of Global Warming's Topic - Anggian Anggraeni; Kholifah Kholifah; Suliyanah Suliyanah (Universitas Lambung Mangkurat, 2024)
Implementation of one learning model in the classroom will stimulate student learning outcomes. Class X-1 at SMA Negeri 13 Surabaya shows that student learning outcomes must be upgraded based on the researcher’s observation. The objective of fulfilling the Problem-Based Learning model with the Lesson Study approach in this research is to upgrade the cognitive competencies and the value of learning in class X-1 SMA Negeri 13 Surabaya. This type of research is Classroom Action Research, with a total research target of 36 students in class X-1 SMA Negeri 13 Surabaya. The teacher conducts learning for three cycles on global warming material, with each cycle using a lesson study approach. Research data was attained from observer observations and data on students' cognitive abilities. Then, it was analyzed to define the percentage of learning completion and the intensification of cognitive competencies using n-gain. The research results show an improvement in cognitive competencies with a value of 0.557 in the moderate category. Apart from that, the research results show an improvement in the percentage of learning operations. Therefore, it can be established that the research directed by the teacher can develop cognitive competencies and the quality of learning in class X-1 SMA Negeri 13 Surabaya.